A single nanofluorophore "turn on" probe for highly sensitive visual determination of environmental fluoride ions. Issue 16 (27th February 2018) - Li, Yangjie; Sun, Qin; Su, Lei; Yang, Linlin; Zhang, Jian; Yang, Liang; Liu, Bianhu; Jiang, Changlong; Zhang, Zhongping
Abstract : A single nanofluorophore "off–on" probe based on the unique fluoride–boron interaction to achieve the highly sensitive visual determination of fluoride ions. Abstract : Herein, we report a single nanofluorophore "off–on" probe based on the unique fluoride–boron interaction to achieve the visual determination of fluoride ions in environmental water. Red quantum dots (QDs) were modified using 3-aminophenylboronic acid (APBA) to form a stable standard emission probe, and reaction of the probe with catechol formed a five-membered cyclic borate ester, which led to the quenching of the fluorescence emission. The designed nanofluorophore probe showed a turn-on effect in the presence of fluoride ions due to the five-membered cyclic borate ester being transformed into a trifluoroborate, with breakage of the B–O bonds and removal of the catechol from the QDs. The prepared nanofluorophore probe displayed a high sensitivity for the quantification of fluoride ions with a naked eye visual detection limit of 0.4 μM, which was much lower than the US Environmental Protection Agency (EPA) defined limit (37 μM). Furthermore, the probe displayed an effective application for the detection of fluoride ions in environmental samples such as tap water and lake water. The very simple method reported here could be extended to the visual detection of a wide range of analysis assays in natural samples.